A Fresh Start for the Objective-List Theory of Well-Being. Issue 2 (28th June 2013) - FLETCHER, GUY
Abstract : So-called 'objective-list' theories of well-being (prudential value, welfare) are under-represented in discussions of well-being. I do four things in this article to redress this. First, I develop a new taxonomy of theories of well-being, one that divides theories in a more subtle and illuminating way. Second, I use this taxonomy to undermine some misconceptions that have made people reluctant to hold objective-list theories. Third, I provide a new objective-list theory and show that it captures a powerful motivation for the main competitor theory of well-being (the desire-fulfilment theory). Fourth, I try to defuse the worry that objective-list theories are problematically arbitrary and show how the theory can and should be developed.